Tinjauan Kriminologis Penyalahgunaan Dextromethorphan (Dmp) Yang Dijual Bebas Di Apotek Yang Dilakukan Oleh Remaja Di Kabupaten Jepara (Studi Kasus Di Polres Jepara) - Ardiyanto, Dedy Nor; , Dr. Natangsa Surbakti, SH., M.Hum (2016)
This study aims to determine the factors behind the abuse of dextromethorphan by young people in the district of Jepara and to know the efforts made by the police forces and the Police Jepara obstacles in tackling abuse of dextromethorphan by young people in the district of Jepara. The research method using descriptive empirical jurisdiction. Sources of primary data, interviews and secondary data sources of primary law, secondary and tertiary. Data were collected by interview and literature study then analyzed the data qualitatively. The results showed that the factors underlying that there are two internal personality and curiosity / desire to try from teenage self and the external environment, whether family, community and youth education factor. Efforts made by the Police Police Jepara in overcoming it through two stages of prevention that consists of pre-emptive actions and preventive actions, then the second stage through the efforts of repressive action. Barriers that prevent the police consists of internal barriers that the number of personnel who do not meet the Drug Sat, leaking of information and lack of funds. While the external constraints that rule of law is less clear on the abuse of dextromethorphan, a lack of awareness of stakeholders (pharmacies and Health Agency), and people who are less cooperative with the police.